Analisis Pertumbuhan BAL dan Khamir pada Masa Fermentasi Sourdough dengan Penambahan Sari Buah Markisa - Miftahul Jannah; Rizki Amelia Nasution; Ulfayani Mayasari (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to determine the growth of lactic acid bacteria (LAB) and yeast during Sourdough fermentation with the addition of passion fruit juice (Passiflora edulis Sims). Sourdough is a fermented dough used as a natural leavening agent in bread making; however, its non-specific aroma is considered one of its weaknesses and reduces consumer interest. The addition of passion fruit juice was intended to improve the aroma characteristics of Sourdough due to the fruit’s distinctive and strong aroma. The methods used in this study included total lactic acid bacteria count and total yeast count to analyze microbial growth during fermentation. The results showed that the populations of LAB and yeast changed throughout the fermentation process in each treatment. The highest LAB count was obtained in treatment P2 on the fifth day, reaching 248.34 × 10⁷ CFU/ml, while the highest yeast  count  was  found  in  treatment  P3  on  the fifth day, reaching 130.01 × 10⁷ CFU/ml. In conclusion, the addition of passion fruit juice affected the microbial dynamics during Sourdough fermentation. The concentration of passion fruit juice and fermentation time played important roles in the growth of LAB and yeast in Sourdough.  Keywords: Lactic Acid Bacteria, Fermentation, Yeast, Sourdough